PENGARUH RASIO KEUANGAN TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Amar, Siti Salama; Nurfadila, Diah (JURNAL AKUNTANSI DAN INVESTASI, 2017)
Estimation of earnings can be done by analyzing the financial statements, namely the form of calculations and interpretations through the financial ratio. Goal of this research conducted by researchers is to provide empirical evidence: (1) to determine the effect of WCTA, DER, TAT, and NPM partially on growth profit (2) to know the effect of WCTA, DER, TAT, and NPM simultaneously to profit growth. This research uses sample determination technique with purposive sampling, the criteria used as follows: (1) Manufacturing company listed in Indonesia Stock Exchange (BEI) in period 2014-2016 (2) Company that publishes complete financial report from period 2014-2016 (3) Companies that use rupiah currency units in the financial statements (4) Companies with net profit in the period 2014-2016. The results of this study are: (1) Working capital to total assets does not significantly influence profit growth, (2) Debt to Equity does not significantly influence profit growth, (3) Total asset turnover does not significantly affect profit growth, (4) Net profit margin has no significant effect to profit growth, (5) Based on F test result (simultaneous) that independent variable that is working capital to total asset, debt to equity ratio, total asset turnover and net profit margin simultaneously have no effect significant to profit growth